Effects of immersion and navigation agency in virtual environments on emotions and behavioral intentions - Weller, René; Cepok, Joscha; Arzaroli, Roman; Marnholz, Kevin; Große, Cornelia S.; Reuter, Hauke; Zachmann, Gabriel (Frontiers in Virtual Reality, 2022)
We present a study investigating the question whether and how people's intention to change their environmental behavior depends on the degrees of immersion and freedom of navigation when they experience a deteriorating virtual coral reef. We built the virtual reef on top of a biologically sound model of the ecology of coral reefs, which allows us to simulate the realistic decay of reefs under adverse environmental factors. During their experience, participants witness those changes while they can also explore the virtual environment. In a two-factorial study (N = 224), we have investigated the effects of different degrees of immersion and different levels of navigation freedom on emotions, the feeling of presence, and participants' intention to change their environmental behavior. The results of our analyses show that immersion and navigation have a significant effect on the participants' emotions of sadness and the feeling of helplessness. In addition, we found a significant effect, mediated by the participants' emotions, on the intention to change their behavior. The most striking result is, perhaps, that the highest level of immersion combined with the highest level of navigation did *not* lead to the highest intentions to change behavior. Overall, our results show that it is possible to raise awareness of environmental threats using virtual reality; it also seems possible to change people's behavior regarding these threats. However, it seems that the VR experience must be carefully designed to achieve these effects: a simple combination of all affordances offered by VR technology might potentially decrease the desired effects.